2021
DOI: 10.3389/fmicb.2021.696604
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Molecular Biology of Human Bocavirus 1 and Its Applications

Abstract: Human bocavirus 1 (HBoV1) was discovered in human nasopharyngeal specimens in 2005. It is an autonomous human parvovirus and causes acute respiratory tract infections in young children. HBoV1 infects well differentiated or polarized human airway epithelial cells in vitro. Unique among all parvoviruses, HBoV1 expresses 6 non-structural proteins, NS1, NS1-70, NS2, NS3, NS4, and NP1, and a viral non-coding RNA (BocaSR), and three structural proteins VP1, VP2, and VP3. The BocaSR is the first identified RNA polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 118 publications
0
35
0
Order By: Relevance
“…NS1 contains three functional domains, including the N-terminal DNA-binding/endonuclease domain, a helicase domain in the middle, and the C-terminal transcription activation domain, in which the endonuclease and helicase domains are essential to viral DNA replication ( 28 , 68 , 69 ). We noted that it was difficult to purify the large mass of the NS1 protein (NS1-100) in bacteria; thus, we chose to purify the short isoform of NS1, i.e., the NS1-70 protein, which contains the endonuclease and helicase domains and is sufficient to induce a DDR ( 57 ) for an assessment of its interaction with Ku70.…”
Section: Resultsmentioning
confidence: 99%
“…NS1 contains three functional domains, including the N-terminal DNA-binding/endonuclease domain, a helicase domain in the middle, and the C-terminal transcription activation domain, in which the endonuclease and helicase domains are essential to viral DNA replication ( 28 , 68 , 69 ). We noted that it was difficult to purify the large mass of the NS1 protein (NS1-100) in bacteria; thus, we chose to purify the short isoform of NS1, i.e., the NS1-70 protein, which contains the endonuclease and helicase domains and is sufficient to induce a DDR ( 57 ) for an assessment of its interaction with Ku70.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five substitutions in NS1 protein found in our samples, two are located in the middle helicase domain [ 9 ] but fall outside of four conserved Walker motifs which execute 3′–5′ helicase function [ 9 , 40 ]. Three substitutions are located in the C-terminal part of NS1 protein, which is predicted to have transcription transactivation capability, but has not been studied [ 9 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…HBoV possess a linear, single-stranded DNA genome of 5543 nucleotides (nt) long with non-identical terminal hairpins of 140 and 122 nt that play a key role in virus replication [ 7 , 8 ]. Recent advances in molecular biology research of HBoV1 revealed that during its replication in the polarized/nondividing airway epithelial cells HboV1 expresses six nonstructural proteins: NP1, NS1, NS1-70, NS2, NS3, and NS4, depending on splicing mRNAs within ORF 1 [ 9 ]. The mRNA spliced at the D2-A2 sites results in a shift of the NS1 ORF at the C-terminus and encodes NS1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations